3D finite element model for predicting manufacturing distortions of composite parts. (November 2016) - Çınar, Kenan; Ersoy, Nuri
A 3D finite element model has been developed for predicting manufacturing distortions of fibre-reinforced thermosetting composite parts. The total curing process is divided into three steps that correspond to the states that resin passes through during curing: viscous, rubbery, and glassy. Tool–part interaction properties were calibrated by modelling the distortion of a single ply part. For comparison, composite parts of various geometries (L-section and U-section), stacking sequences, thicknesses, and bagging conditions were manufactured. The full field thickness profile and full field distortion pattern were obtained using a 3D laser scanner, which reveals higher and lower resin bleeding and corner thickening locations. The effect of stacking sequence is also examined with the full field distortion pattern. It was found that the parts manufactured under the bleeding condition give higher spring-in and warpage values. The spring-in predictions were well matched to measurements of the manufactured parts.